KEWIRAUSAHAAN DALAM PENGELOLAAN BISNIS MIKRO STUDI KASUS GAPOKTAN LESTARI SEJAHTERA DESA LEMBAHSARI - Ritawiyati Ritawiyati; Sri Maryanti; Muhammad Thamrin (PEKBIS, 2019)
In Lembah Sari village, Rumbai Peisisir Subdistrict, Pekanbaru city is an area wheremost of the population is farming, gardening, fishing, and home business. Based ondata from the kecamatan 2017 BPS, the most extensive land in the Rumbai Pesisirsub-district is the valley sari village area compared to other village villages. With theuse of vacant land in the area, the community wants to cultivate land for agriculture,ponds and livestock. Based on interviews with the chairman of GAPOKTAN, not allland is vacant, farmers can use it, because some of the vast land is owned byseveral people which is only for investment in the form of land without thinking to beutilized. while some farmer groups in the area expect to be able to manage andcultivate the land and can produce the expected yields, in this case one that is anobstacle to the interest of members of farmer groups to be active in their activities,which eventually from some farmer groups is inactive and entrepreneurial spirit inmanagement business is lacking, even there is no motivation to manage the farmergroup well. The research objective was to find out and explore the potential andentrepreneurial motivation of Gapoktan Lestari Sejahtera LembahSari Village. Theresearch method used is descriptive method with an internal factor approach andexternal factors in entrepreneurship. Types and sources of data used primary andsecondary data. The results of the study, based on the Integrated EntrepreneurshipInternal Factors of Sustainable Farmers Group, that courage, hard work, courage infacing business risks, the results strongly agree in the sense that members of farmergroups have an entrepreneurial spirit to be able to develop their business while theleadership ability and capital are less supportive this is because in terms of formaleducation the category of most members of farmer groups is elementary and juniorhigh school. From formal education can influence the mindset in entrepreneurshipand communication. Based on the results of research from ExternalEntrepreneurship factors, both support from the family, friends, village officials arevery encouraging and well motivated regarding the existence of the SustainableFarmers Group Joint business activities in Lembahsari Village.